2020
DOI: 10.2188/jea.je20190199
|View full text |Cite
|
Sign up to set email alerts
|

Heated Tobacco Product Smokers in Japan Identified by a Population-Based Survey

Abstract: Background: In this study, we aim to estimate the prevalence of heated tobacco product (HTP) smokers 3 years after the launch of HTPs in Japan. Methods: Our study, performed in February 2018 in Japan, had a cross-sectional population-based design. A total of 4,628 adult participants (2,121 men and 2,507 women) were randomly sampled from all regions of Japan. The response rate was 57.9%. Interviews were conducted by trained investigators who visited participants' homes. A survey on current (past 30 days) and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…The prevalence of current HTP users among Korean adults reached 4.4.% a year after its introduction in Korea—a much higher rate than those of Italy, United States, or Great Britain, but similar to Japan’s 4 - 7 . Although this confirmed that HTPs are relatively more popular in East Asian countries, it should be interpreted cautiously, as their introduction time is different for various countries.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The prevalence of current HTP users among Korean adults reached 4.4.% a year after its introduction in Korea—a much higher rate than those of Italy, United States, or Great Britain, but similar to Japan’s 4 - 7 . Although this confirmed that HTPs are relatively more popular in East Asian countries, it should be interpreted cautiously, as their introduction time is different for various countries.…”
Section: Discussionmentioning
confidence: 93%
“…The rate of current HTP use was 5.0% among Japanese adults in 2018 4 . In 2017, 1.4% of Italian adults were ever users of HTPs 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Among adult women, those who were 20-39 years old, with 15 or fewer years of education, with a household size of three or more people, employed or self-employed, current internet users, and with risky behaviors related to alcohol were more likely to use HTPs. 40) 1945 1950 1955 1960 1965 1970 1975 1980 1985 1990 1995 Another Japanese study compared device preference and showed that IQOS was used more by younger people and those who reported daily use. 41) Dunbar et al 42) reported that among young adults in the United…”
Section: Characteristics Of Heated Tobacco Product Usersmentioning
confidence: 99%
“…In one Japanese study, the prevalence of HTP use among adult men was highest among the following groups: individuals aged 20–49 years old, with 10 or more years of education, who were not bereaved or divorced, with high household income, who were current internet users, and with risky behaviors related to alcohol. Among adult women, those who were 20–39 years old, with 15 or fewer years of education, with a household size of three or more people, employed or self-employed, current internet users, and with risky behaviors related to alcohol were more likely to use HTPs [ 40 ]. Another Japanese study compared device preference and showed that IQOS was used more by younger people and those who reported daily use [ 41 ].…”
Section: Trends In Tobacco Use In South Koreamentioning
confidence: 99%
“…Furthermore, Jiang et al showed that miR-21 peripheral blood levels are increased in atherosclerosis, suggesting its potential as a biomarker for CVD 18 . In addition, miR-21 may be a potential biomarker for breast cancer and chronic kidney disease 10 , 19 . Also, Jianhong et al showed that circulating miR-21 is up-regulated at all clinical stages in gastric cancer patients, suggesting that circulating miR-21 level is up-regulated throughout cancer progression 20 .…”
Section: Introductionmentioning
confidence: 99%